Tectono-climatic influence on landscape changes in the glaciated Durung Drung basin, Zanskar Himalaya, India: A geospatial approach. (25th February 2019) - Taloor, Ajay Kumar; Kotlia, Bahadur Singh; Jasrotia, Avtar Singh; Kumar, Ajay; Alam, Akhtar; Ali, Sadiq; Kouser, Beena; Garg, Purushottam Kumar; Kumar, Rajesh; Singh, Anil Kumar; Singh, Bhupinder; Jasrotia, Rakesh
Abstract: This study aims at assessing the tectonic and climatic responses to landscape changes transpired in the Durung Drung basin in the Zanskar Himalaya. We used relevant geomorphic indices interpreted from ASTER DEM satellite data and supplemented by the field observations to decipher active tectonics and resultant changes in the landscape. A N-S trending fault in the north of the basin was studied with the help of basin geometry which includes relative parameter, length area relation, form factor, shape factor ratio, elongation ratio, circulatory ratio, compactness coefficient and morphotectonic indices (e.g., drainage basin asymmetry, mountain front sinuosity, hypsometric integral, topographic symmetric factor) to comprehend the geomorphic signatures of the active tectonics. The geomorphic indices indicate upliftment and tilting of the basin. The data on mountain front index and hypsometric integral reveal the uplift and high relief. We propose that the western side of the basin is tectonically more active than eastern side, suggesting active upliftment. The convex nature of hypsometric curve and strongly elongated circulatory ratio reflect competing role of deformation by tectonics. The results of mountain front index and hypsometric integral reveal high relief and uplift. Overall deglaciation of 12.91% was observed in the basin. Analysis of the meteorological data for the last century (1901–2017) indicate that increase in minimum and maximum temperature coupled with increase in liquid precipitation are probably the main drivers of glacier depletion. We conclude that the drainage system of this basin is structurally controlled and overall landscape change is significantly influenced by the ongoing perturbations in the climate system.